Entwicklung eines neuen Modells zur Analyse regionaler Governanceprozesse. - Nischwitz, Guido; Diller, Christian; Chojnowski, Patrick; Kohl, Martin (Taylor & Francis, 2020)
Based on theoretical considerations on life cycles and multi-level models, this paper presents a new model to describe and analyze the development of regional governance processes on longer timescales. Additionally, elements of the path dependence debate and the resilience concept are included. Given this and a data base of over 1300 regional cooperations in Germany, a regional life and adaption cycle model is formulated, which systematically differentiates four development phases. The focus is laid on “tipping points", that indicate the transition between two phases. Using the Altmark-region as an example, die model is filled with data and consequences for its interpretation are drawn. The model allows the flexible analysis of processes of change and adaptation in multi-level governance structure. External and internal impulses can be distinguished. For each "tipping point", a specific adaptation cycle can be determined in the region, which describes die direction of the effects and the level of resilience reached. However, the new life cycle model has yet to be developed: The aspects of path dependency and resilience as well as die question of conditions for success are not yet sufficiently integrated. The typology of "tipping points" of phase changes should be specified. Therefore, further theoretical considerations and more detailed empirical research are necessary to improve the model.
Development of a new model for the analysis of regional governance processes.
Keywords: Raumordnung; Regionalpolitik; Steuerungsinstrument; Regionalisierung; Regional Governance; Pfadanalyse; Mehrebenenanalyse; Modellentwicklung; Analyseverfahren; Regionale Zusammenarbeit; Empirische Untersuchung; Anwendungsbeispiel; Fallstudie